Tegoprazan‐Containing Versus Proton Pump Inhibitor‐Containing Therapy for First‐Line Eradication of Helicobacter pylori: A Meta‐Analysis of Randomized Controlled Trials - Daniel Martin Simadibrata; Elvira Lesmana; Ivan Damara; Mochammad Izzatullah; Pojsakorn Danpanichkul; Hae Won Yoo; Su Jin Hong; Ari Fahrial Syam (JGH Open)
ABSTRACT Introduction Concerns have been raised regarding the decreasing success rates of the standard treatment of Helicobacter pylori (proton pump inhibitor (PPI) and two/three antibiotics) and the long‐term effects carried by PPI. Despite conflicting data, Tegoprazan, a potassium‐competitive acid blocker, is hypothesized to be superior to PPI for eradicating H pylori. This systematic review and meta‐analysis aim to determine the superiority of Tegoprazan‐containing therapy to PPI‐containing therapy for H pylori eradication. Methods A systematic literature search identified studies published until December 12, 2024, from MEDLINE, EMBASE, SCOPUS, and CENTRAL. The search strategy included the following keywords: “Tegoprazan,” “Proton Pump Inhibitors,” and “Helicobacter pylori.” Only randomized controlled trials (RCTs) that compared the efficacy of Tegoprazan to any PPI were included. Risk of bias assessment was performed using the Cochrane Risk of Bias 2 (RoB2) tool for RCTs. The random‐effect model was used to calculate the pooled risk ratio (RR) and its 95% Confidence Interval (95% CI) from the intention‐to‐treat population. Results Six RCTs with low risks of bias were included in this meta‐analysis. All studies included treatment‐naïve patients and compared first‐line H pylori treatment. The overall eradication rates of Tegoprazan‐containing (N = 1052) versus PPI‐containing therapy (N = 1058) were 83.37% and 80.06%, respectively (RR 1.045; 95% CI 1.008–1.084; I2 = 0%). Tegoprazan‐containing therapy demonstrated comparable treatment‐emergent adverse event (TEAE) rates compared to PPI‐containing therapy (46.48% vs. 46.31%; RR 1.026; 95% CI 0.952–1.106; I2 = 48%). Conclusion This meta‐analysis demonstrated that Tegoprazan‐containing therapy is superior to PPI‐containing therapy for first‐line H pylori eradication, with comparable safety profiles.